Thermolysis of sprayed suspensions for obtaining highly spinel ferrite nanoparticles - Petrova, Elena G.; Shavshukova, Yana A.; Kotsikau, Dzmitry A.; Yanushkevich, Kazimir I.; Laznev, Konstantin V.; Pankov, Vladimir V. (Journal of the Belarusian State University. Chemistry, 2019)
Thermal treatment of ferrite magnetic nanoparticles in NaCl matrix gives an opportunity to increase their specific magnetization with preservation of nanoscale size. Composite materials based on mixed ferrites Co0.65Zn0.35Fe2O4 and Mg 0.5Zn0.5Fe2O4 were synthesized by spray-drying of aqueous suspensions in presence of NaCl and annealed at 300 –900 °C. The microstructure and phase composition of nanoparticles before and after annealing were studied by scanning and transmission electron microscopy (SEM and TEM), X-ray diffraction analysis and IR spectroscopy. The magnetic properties of nanoparticles were estimated using a ponderomotive method of measuring the specific magneti zation at room temperature in a magnetic field with an induction of 0.86 T. The increase of the annealing temperature up to 900 °C was established to lead to the increase in the specific magnetization of ferrites – from 32.79 to 91.3 emu/g (Co0.65Zn0.35Fe2O4) and from 2.76 to 22.31 emu/g (Mg 0.5 Zn 0.5Fe2O4) due to recrystallization processes and increase of crystallinity degree of the ferrites. Due to the NaCl insulating layer, the particle size increases just slightly (from ~ 10 nm before annealing to ~ 60 nm after annealing at 900 °C). This method is effective for substantial increase in specific magnetization of ferrite nanoparticles with preservation of their nanoscale size.
Keywords: magnetic nanoparticles; spinel ferrites; spray-drying; crystallinity; heat treatment